Demon bluźnierstwa w ujęciu Jana Klimaka - Pancerz, Roland Marcin (Vox Patrum, 2014)
Among temptations and impediments, which the monk must face on the path to perfection, John Climacus enumerates blasphemous thoughts. He also names them as assaults of the demon of blasphemy. Frequently man exposes himself to his action through the vice of pride, but it also happens, that this demon attacks ingenuous people that get worried too much. The purpose of the spirit of blasphemy is to insidiously cause feelings of guilt in the human heart; to take a man away from a prayer and the Eucharist; to drive him to despair and hope lessness. According to author’s witness, some people struggled with this problem for their whole life, and in extreme cases its effect was even a state of madness. John Climacus, a good “psychologist” and expert in the spiritual life, clearly emphasizes the fact that the assaults of blasphemous thoughts are beyond a man’s control. In that case he is like a passive listener, whom reach some external voices. Besides, stopping the attacks of such thoughts is almost impossible because they are violent and rapid. Therefore, in the author’s opinion, the traditional methods of struggle against the demon of blasphemy, like severe mortifications and spelling repeatedly various scriptural words, do not get expected results. The only way to beat the enemy is to remain calm and indifferent towards such thoughts. Spiritual direction plays an important role in this matter. The monk still has to overcome shame and confess sincerely his own thoughts to an elder (abba). The duty of the spiritual father, in turn, is to calm down conscience of the disciple, so that he will not worry about the problem anymore. We have to admit that no previous writer speaks in such soothing tone about the blasphemous thoughts.